Hedonic Binging in Indulgent Travel Consumption - Soldat, Zorana (Curtin University, 2017)
The current study conceptualises hedonic binging and examines its impact on tourists’ desire and intention to engage in indulgent travel consumption. Across a pilot and two main studies (N=708), an online survey was self-administered to respondents who had patronised a luxury hotel/resort while on vacation. Theoretically, the proposed decision-making framework gives researchers more insight into hedonic binging in the tourism context. Managerially, the proposed impulsive-compulsive continuum helps practitioners to identify and address indulgence-seeking tourist segments.